2023
DOI: 10.1371/journal.pone.0280236
|View full text |Cite
|
Sign up to set email alerts
|

Croatian national audit on videolaryngoscopes and alternative intubation devices in the era of COVID-19 pandemic

Abstract: Introduction Videolaryngoscopy (VL) is the recommended strategy for airway management in COVID-19 patients and guidelines recommends that all anesthesiologists should be trained to use and have immediate access to the device. However, the availability of VL in hospitals and its use may vary, as well as the choice of the device and necessary training. Our primary aim was to investigate data on availability of VL in Croatia, its use, the choice of the device and its implementation, with special consideration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The results of the INTUBE study (17% videolaryngoscope use) 28 support the initial low baseline, but the relatively small absolute increase at the point of survey completion is surprising. It is, however, mirrored in the Croatian institutional survey of videolaryngoscope use during the pandemic, where routine videolaryngoscope use rose from 16% to 21% on COVID wards, 29 and the survey of EAMS (European Airway Management Society) members which reported an increase in routine use of 12.5% to 38.9%. 25 Conversely, Granell Gil et al's survey of 1125 Spanish clinicians in the early phase of the pandemic (April/May 2020) reported that 70.5% of respondents would choose a videolaryngoscope to intubate COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the INTUBE study (17% videolaryngoscope use) 28 support the initial low baseline, but the relatively small absolute increase at the point of survey completion is surprising. It is, however, mirrored in the Croatian institutional survey of videolaryngoscope use during the pandemic, where routine videolaryngoscope use rose from 16% to 21% on COVID wards, 29 and the survey of EAMS (European Airway Management Society) members which reported an increase in routine use of 12.5% to 38.9%. 25 Conversely, Granell Gil et al's survey of 1125 Spanish clinicians in the early phase of the pandemic (April/May 2020) reported that 70.5% of respondents would choose a videolaryngoscope to intubate COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%